2021
DOI: 10.1038/s41598-021-91481-z
|View full text |Cite|
|
Sign up to set email alerts
|

Saharan dust and giant quartz particle transport towards Iceland

Abstract: Mineral dust emissions from Saharan sources have an impact on the atmospheric environment and sedimentary units in distant regions. Here, we present the first systematic observations of long-range Saharan dust transport towards Iceland. Fifteen Saharan dust episodes were identified to have occurred between 2008 and 2020 based on aerosol optical depth data, backward trajectories and numerical models. Icelandic samples from the local dust sources were compared with deposited dust from two severe Saharan dust eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 99 publications
0
33
0
1
Order By: Relevance
“…
Because all these impacts depend sensitively on dust size , global aerosol models need to accurately represent the dust particle size distribution (PSD) to quantify the various dust impacts on the Earth system. Recent dust PSD measurements have indicated that super coarse (diameter >10 μm) dust particles are more prevalent than previously thought (Ryder et al, 2018(Ryder et al, , 2019 van der Does et al, 2018;Varga et al, 2021). Indeed, recent model estimates suggest an atmospheric load of ∼10 Tg of super coarse dust, which represents about a quarter of the total atmospheric loading of particulate matter and adds an estimated warming effect of around 0.10 W m −2 by absorbing both short-wave and long-wave radiation (
…”
mentioning
confidence: 97%
“…
Because all these impacts depend sensitively on dust size , global aerosol models need to accurately represent the dust particle size distribution (PSD) to quantify the various dust impacts on the Earth system. Recent dust PSD measurements have indicated that super coarse (diameter >10 μm) dust particles are more prevalent than previously thought (Ryder et al, 2018(Ryder et al, , 2019 van der Does et al, 2018;Varga et al, 2021). Indeed, recent model estimates suggest an atmospheric load of ∼10 Tg of super coarse dust, which represents about a quarter of the total atmospheric loading of particulate matter and adds an estimated warming effect of around 0.10 W m −2 by absorbing both short-wave and long-wave radiation (
…”
mentioning
confidence: 97%
“…of South America. Thus, the picture of the Saharan dust spread during the period under consideration outlines a dust episode with exceptional strength and extent, significantly exceeding the heavy dust outbreaks typical for this period of the year [26,58,59].…”
Section: Nmmb/bsc-dust Global Dust Model Forecastsmentioning
confidence: 96%
“…These tremendous amounts of dust are transported by air circulation systems thousands of kilometers across the Atlantic to North and South America, as well as to Europe and the Middle East [13,[18][19][20][21][22][23]. A considerable part of these dust emissions crosses the Mediterranean and reaches mostly Southern and Central Europe, and less often the northern parts of the continent [10,13,[23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Основными источниками почвенной пыли являются крупные засушливые районы мира: Африканский континент, особенно пустыня Сахара, Аравийский полуостров и Азия (восточные районы). Частицы почвенной пыли, возникшие в этих районах, могут переноситься на большие расстояния под действием сильных ветров и конвективных процессов ; van der Does et al, 2018; Yu et al, 2019;Varga et al, 2021).…”
Section: Introductionunclassified